INKLUSIFISME ISLAM DI INDONESIA - Amir Gufron (UIN Raden Mas Said Surakarta, 2014)
Inclusivism as one of several approaches to understanding the relationshipbetween religions, asserts that while one set of beliefs is true, other sets of beliefs are atleast partially true. This concept also put the precedence kind of thought and not theprejudice. Inclusivism would be a logical consequence as the logic of universal humanityis inclusivism itself. In response to the question of the truth of religious traditions, wecan use some of the principal approaches, namely: exclusivism, inklusivism, andpluralism. The exclusivism’s view is very extreme, because it claims that the truth isjust on their own. While pluralism is a moderate form of relativism in which says thatall religions are true. It is very important to grow inclusivism in religion in this casefor its followers. This is in accordance with the recommendation ulama' (isamicscholars of 'NU) in National Conference of Ulama’ on 15-16 November 1997 inCilacap, central Java.